Omni-directional wideband circularly polarized planar antennas for wireless communications - Roshini, John (2016)
With the advancement in communication systems the need for broader bandwidth and good quality of performance has increased. This dissertation proposes two novel monopole antennas for wideband circularly polarized and omnidirectional radiation fed for wireless system applications. The antenna consists of a trapezoidal-shaped radiator with a meandered ground plane fed by a single microstrip feed line. Initially a narrow band antenna is designed to first achieve the circular polarized and omnidirectional behaviour and from there the other two wideband antennas are designed. Both the wideband antennas proposed in this thesis have a good wideband behaviour. Where the first antenna exhibits 40% axial-ratio bandwidth while the second antenna has a bandwidth of 58%. The antenna exhibiting 40% bandwidth has an overall antenna size of 38.0 mmx 40.0 mmx 0.8 mm with a maximum gain of 2 dBi. The antenna is fabricated and compared with the simulated results. Also a parametric study on this antenna is conducted as well. While the second antenna of size 29.0 mmx 40.0 mmx 0.8 mm also exhibiting a maximum gain of 2 dBi is designed from the results attained from the parametric study for the first .The future of the second antenna would be to assess it for fabrication and compare its results as well. Therefore to conclude, it can be stated that the objective of the thesis of designing a wideband, circular polarized, omnidirectional antenna is successfully designed by fulfilling all the requirements.